PENGARUH GAYA HIDUP, LOKASI, DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN DI CAFE FR92 BALIKPAPAN - Trie Wahyuni, Irma; Sukimin, Sukimin (MEDIA RISET EKONOMI [MR.EKO], 2026)
The purpose of this study was to determine the effect of lifestyle, location and price both simultaneously and partially on purchasing decisions. This research uses quantitative research methods by collecting data through questionnaires, interviews, observations and also supported by secondary data. The sampling technique in this study was the probability sampling technique which consisted of 317 respondents. This study uses several analytical methods, including; validity test, reliability test, classic assumption test, multiple linear regression test, the hypothesis is tested by F test and t test. The results of the F test show that Lifestyle (X1), Location (X2) and Price (X3) have a significant influence simultaneously on Purchase Decision. Meanwhile, in the t test, Location (X2) and Price (X3) have a significant influence on purchasing decisions partially, but Lifestyle (X1) does not have a significant effect on Purchase Decisions. Keywords: 1st Lifestyle; 2nd Location; 3rd Price; 4th Purchase Decision